Communication Strategy of North Lombok District Disaster Board During Earthquake 2018 - wayan Suadnya; Eka Putri Paramitha (JCommsci - Journal Of Media and Communication Science, 2018)
Effective communication is essential in disaster management. Effectif communication is formed when accurate communication strategies is implemented. During the emergency phase of North Lombok District  (KLU) natural disaster earthquake strick effectif communication was not carried out asthe theory of communication strategies. This was due to the KLU District Disaster Management board (BPBD) not yet ready withwritten and web and internet based communication strategies. Information crisis during the emergency period was  conventionally handledtherefore data and informasion collection and analisis less accuratecaulead to slow distribution of data and information to publick and users. As a result casualties rescue and managementslow and inadequate, unequal,unfair and overlaping. Therefore for the up comming future BPBD KLUhas to have good written web and internet based communication strategies. Keywords: Communication, strategy, disaster, Lombok.